Combination of low intensity electromagnetic field with chondrogenic agent induces chondrogenesis in mesenchymal stem cells with minimal hypertrophic side effects. (2nd April 2020) - Hesari, Roya; Keshvarinia, Mina; Kabiri, Mahboubeh; Rad, Iman; Parivar, Kazem; Hoseinpoor, Hoorieh; Tavakoli, Rezvan; Soleimani, Masoud; Kouhkan, Fatemeh; Zamanlui, Soheila; Hanaee-Ahvaz, Hana
ABSTRACT: Background : There are different methods to develop in vitro neo-chondral tissues from adipose-derived stem cells (ADSCs). Application of electromagnetic field (EMF) on ADSCs is one of popular approaches, which results in chondrogenesis. If chondrogenic impact of EMF on ADSCs is supposed to be generalized as a protocol in translational medicine field, possible emergence of early or late hypertrophic maturation, mineralization and inflammatory side effects in chondrogenically differentiating ADSCs should be considered. Methods : The advent of chondrogenic and hypertrophic markers by differentiated cells under standard, platelet-rich plasma (PRP)-based or EMF treatments were monitored. Along with monitoring the expressions of chondrogenic markers, inflammatory and hypertrophic markers, VEGF/TNFα secretion, calcium deposition and ALP activity were evaluated. Results : Accordingly, treatment with %5 PRP results in higher GAG production, enhanced SOX9 transcription, lowered TNFα and VEGF secretions compared to other treatments. Although PRP up-regulates miR-146a and miR-199a in early and late stages of chondrogenesis, respectively, application of EMF + PRP down regulates miR-101 and -145 while up-regulates miR-140 and SOX9 expression. Conclusion : Comparing our results with previous reports suggests that presented EMF-ELF in this study with f = 50 Hz, EMF intensity of less than 30 mT, and 5% PRP (v/v), would facilitate chondrogenesis via mesenchymal stem cells with minor inflammation and hypertrophic maturation. Abbreviations: MSCs: mesenchymal stem cells; TGFβ: transforming growth factor-beta; PRP: platelet-rich plasma; ELF-EMF: extremely low-frequency electromagnetic fields; GAGs: glycosaminoglycans; ADSCs: adipose-derived stem cells; VEGF: vascular endothelial growth factor; TNFα: tumor necrosis factor alpha; ALP: alkaline phosphatase